Navigating big finance and big technology for global change: the impact of social finance on the world's poor - Peterson, Gayle H.; Yawson, Robert; Joan, E.; Nicholls, Jeremy (Palgrave studies in impact finance, 2020)
The role of big finance and technology in social change is rapidly evolving. This book examines why large financial players are entering the social sector through social finance. Drawing on empirical research, the authors analyse the opportunities this new interest and commitment presents as well as the potential harm that can be done to vulnerable people when beneficiaries are not treated as partners and the social needs of people are not placed at the centre of the investment model. This book introduces a ‘Deliberate Leadership’ framework to help big finance tackle problems with no easy solutions. The book also analyses how current technologies (including blockchain) are being used and the benefits and drawbacks of different features of these technologies from the standpoint of the beneficiary and investor. The authors derive a series of insights into the model of technology for social finance and impact investing. Written as a practical book for students alongside a field book based on an action learning methodology, this volume will be useful to those in social finance and impact investing.
Keywords: Réservé UdeM; Social finance